A clínica do autismo e o objeto voz: uma leitura psicanalítica - Correia, Rosângela de Faria (2018)
This dissertation aims to do a reflection, from the clinical-institutional experience, together with a children diagnosed with autism. The crucial point of this study is about the clinical enigma, caused during the meeting with the patient, especially about difficults in language acquisition and absence of voice. In the autisms we can identify phenomena that reveal a difficult for the children to occupy the enunciation place, resulting a position of segregation. This way, considering the relation between the children with their objects, and more specifically with voice object, this research looks for presenting a clinical-theoric reading, articulating the concepts of subjective constitution, body constitution and establishment of pulsional circuits, emphasizing the importance of the voice as an object connected to the desire